A new species of Saxifraga (Saxifragaceae) from northeastern Anatolia, Turkey - Gürcan, Betül; Düşen, Olcay; Kaya, Ergun (Phytotaxa, 2023)
Saxifraga kavrunensis, a new species endemic to Turkey, is described and illustrated. Samples from its natural population were collected from the Kaçkar Mountains in Rize Province. Although it has similar features to S. paniculata subsp. paniculata, it differs in its longer multi-flowered stem and maroon-spotted corolla. In this study, the diagnostic characteristics of S. kavrunensis were elucidated at the morphological, micromorphological and molecular level. In the molecular-based phylogenetic analyses, S. kavrunensis was compared with S. paniculata subsp. paniculata, to which it bears the closest morphological resemblance. After PCR analyses, reproductive band profiles were obtained from three of the eighteen ISSR primers tested. The 66 polymorphic band profiles, ranging from 230 bp to 4000 bp, were obtained from the agarose gel electrophoresis images of these three primers. According to a distance matrix based on the Jaccard coefficient, significant variation was detected at the species level, with indices varying between 0.395 and 0.614 between both species.